2018
DOI: 10.1136/bmjopen-2017-016058
|View full text |Cite
|
Sign up to set email alerts
|

SecurAstaP trial: securement with SecurAcath versus StatLock for peripherally inserted central catheters, a randomised open trial

Abstract: ObjectivesTo assess the effect on needed nursing time for dressing change.Design, setting, participantsA parallel-group, open-label, randomised controlled trial in patients who are in need for a peripherally inserted central catheter insertion in one teaching hospital in Belgium. The follow-up lasted 180 days or until catheter removal, whatever came first. A computer generated table was used to allocate devices. Randomised patients were 105 adults (StatLock, n=53; SecurAcath, n=52) and primary analysis was bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 9 publications
1
21
0
2
Order By: Relevance
“…Only one study directly compared SecurAcath with a competitor product (StatLock); this was a randomised controlled trial (RCT) focusing on the time taken to change a dressing [ 9 ]. Three studies evaluated SecurAcath without a comparator, [ 10 12 ] reporting catheter-related adverse events such as migration and dislodgement.…”
Section: Review Of Clinical and Economic Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…Only one study directly compared SecurAcath with a competitor product (StatLock); this was a randomised controlled trial (RCT) focusing on the time taken to change a dressing [ 9 ]. Three studies evaluated SecurAcath without a comparator, [ 10 12 ] reporting catheter-related adverse events such as migration and dislodgement.…”
Section: Review Of Clinical and Economic Evidencementioning
confidence: 99%
“…The EAC critically appraised these studies and presented a narrative review of how they reported the clinical effectiveness of SecurAcath. Eleven studies were deemed to have ‘low’ relevance to the decision problem; six studies were deemed to have ‘medium’ relevance; and one study ‘medium/high’ relevance (the only RCT comparing SecurAcath to a comparator, StatLock) [ 9 ].…”
Section: Review Of Clinical and Economic Evidencementioning
confidence: 99%
See 3 more Smart Citations